2013
DOI: 10.1371/journal.pntd.0002006
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leishmania RNA Virus in Leishmania Parasites

Abstract: BackgroundPatients suffering from cutaneous leishmaniasis (CL) caused by New World Leishmania (Viannia) species are at high risk of developing mucosal (ML) or disseminated cutaneous leishmaniasis (DCL). After the formation of a primary skin lesion at the site of the bite by a Leishmania-infected sand fly, the infection can disseminate to form secondary lesions. This metastatic phenotype causes significant morbidity and is often associated with a hyper-inflammatory immune response leading to the destruction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 29 publications
6
94
0
Order By: Relevance
“…1B), with little background staining evident in immunofluorescence microscopy. Under these conditions and as seen in previous immunofluorescence studies (36), LgyLRV1 + showed a strong, homogeneous LRV1 distribution (Fig. 1A).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…1B), with little background staining evident in immunofluorescence microscopy. Under these conditions and as seen in previous immunofluorescence studies (36), LgyLRV1 + showed a strong, homogeneous LRV1 distribution (Fig. 1A).…”
Section: Resultssupporting
confidence: 86%
“…RT-PCR tests were performed using LRV1-specific primers (SMB4647 5′-TBRTWGCRCACAGTGAY-GAAGG and SMB4648 5′CWACCCARWACCABGGBGCCAT) or β-tubulin mRNA (SMB5023 5′-AACGCTATATAAGTATCAGTTTCTGTACTTTA and SMB2110 5′-GACAGATCTCATCAAGCACGGAGTCGATCAGC). qRT-PCR was performed as previously described (36), with a 123-bp fragment of LRV1 capsid mRNA amplified with primers SMB5335 (5′-CTGACTGGACGGGGGGTAAT) and SMB5336 (5′-CAAAACACTCCCTTACGC), and a 100-bp fragment of KMP-11 (a Leishmania housekeeping gene) with primers SMB5548 (5′-GCCTGGATGAGGAGTTCAACA) and SMB5549 (5′-GTGCTCCTTCATCTCGGG). The reaction used Power SYBR Green (Applied Biosystems) in an ABI Prism 7000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The monoclonal anti-dsRNA J2 antibody binds dsRNAs at least 40 bp long in a sequence-independent fashion (12)(13)(14). The J2 dsRNA monoclonal antibody was previously used to detect viral dsRNA by dsRNA immunoblotting, immunohistochemistry, ELISA, and immunoprecipitation in eukaryotic cells (13)(14)(15)(16)(17)(18)(19)(20). In this study, we used the J2 dsRNA antibody in an immunoprecipitation assay to enrich dsRNA from total RNA extracted from E. coli.…”
Section: Resultsmentioning
confidence: 99%
“…Lbr siRNAs bear a 5′-P and 3′-OH, reflecting their origin through the action of cellular Dicer nucleases (39), and we used these properties to make siRNAfocused sRNA (<42 nt) libraries for next-generation sequencing (Table S1). For Lgy, we chose the established LRV1 + Lgy M4147 strain (7), and three different Lbr shown to bear LRV1 by PCR and/ or anti-dsRNA antibody tests (40).…”
Section: Resultsmentioning
confidence: 99%